Compassion fatigue in pediatric hematology, oncology, and bone marrow transplant healthcare providers: An integrative review. Issue 6 (December 2022) - Berger, Rebecca S.; Wright, Rebecca J.; Faith, Melissa A.; Stapleton, Stacie
Abstract: Objective: Compassion fatigue (CF), which includes burnout and secondary traumatic stress, is highly prevalent among healthcare providers (HCPs). Ultimately, if left untreated, CF is often associated with absenteeism, decreased work performance, poor job satisfaction, and providers leaving their positions. To identify risk factors for developing CF and interventions to combat it in pediatric hematology, oncology, and bone marrow transplant (PHOB) HCPs. Methods: An integrative review was conducted. Controlled vocabulary relevant to neoplasms, CF, pediatrics, and HCPs was used to search PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycINFO, and Web of Science MEDLINE. Inclusion criteria were the following: English language and PHOB population. Exclusion criteria were the following: did not address question, wrong study population, mixed study population where PHOB HCPs were only part of the population, articles about moral distress as this is a similar but not the same topic as CF, conference abstracts, and book chapters. Results: A total of 16 articles were reviewed: 3 qualitative, 6 quantitative, 3 mixed methods, and 4 non research. Three themes were explored: (1) high-risk populations for developing CF, (2) sources of stress in PHOB HCPs, and (3) workplace interventions to decrease CF. Significance of results: PHOB HCPs are at high risk of developing CF due to high morbidity and mortality in their patient population. Various interventions, including the use of a clinical support nurse, debriefing, support groups, respite rooms, and retreats, have varying degrees of efficacy to decrease CF in this population.